1999
DOI: 10.2169/internalmedicine.38.31
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 1,25-dihydroxyvitamin D Supplementation on Blood Pressure Reduction in a Pseudohypoparathyroidism Patient with High Renin Activity.

Abstract: A 42-year-old manhad biochemical and somatic abnormalities compatible with pseudohypoparathyroidism type I (PsHP) and also had high plasma renin activity (PRA). After 1,25-dihydroxyvitamin D (calcitriol) supplementation the systolic/diastolic blood pressure, assessed by 24-hour non-invasive ambulatory blood pressure monitoring, was reduced from 145/96 mmHg to 128/85 mmHg with normalization of the serum calcium level and its related hormones, as well as decreased PRA. Calcitriol supplementation successfully red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 18 publications
2
33
0
1
Order By: Relevance
“…In addition, vitamin D could modulate lipid levels via suppression of PTH secretion, as elevated PTH concentrations reportedly reduce lipolysis (30). Secondly, the blood pressure may be influenced by vitamin D through regulation of the renin-angiotensin system, an important regulator of blood pressure (31,32). Last, experimental studies have suggested that vitamin D may exert its beneficial effects by stimulating the expression of an insulin receptor to improve insulin responsiveness for glucose transport or by controlling calcium influx, which is essential for the insulin-mediated intracellular process in insulin-responsive tissues (33).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, vitamin D could modulate lipid levels via suppression of PTH secretion, as elevated PTH concentrations reportedly reduce lipolysis (30). Secondly, the blood pressure may be influenced by vitamin D through regulation of the renin-angiotensin system, an important regulator of blood pressure (31,32). Last, experimental studies have suggested that vitamin D may exert its beneficial effects by stimulating the expression of an insulin receptor to improve insulin responsiveness for glucose transport or by controlling calcium influx, which is essential for the insulin-mediated intracellular process in insulin-responsive tissues (33).…”
Section: Resultsmentioning
confidence: 99%
“…Mice without the vitamin D-activating 1α-hydroxylase develop hyperreninaemia, independently of calcium levels [20]. The administration of calcitriol (1,25[OH] 2 D 3 ), the active hormonal metabolite of vitamin D, or its analogues, reduces plasma renin activity and angiotensin II levels in experiments and in humans [21,22]. Vitamin D status has shown inverse relationships with plasma renin activity in humans [23,24], while activated vitamin D and AT 1 receptor antagonism have synergistic beneficial effects on RAS regulation and on outcomes in diabetic nephropathy [25].…”
Section: -Hydroxyvitamin D (25[oh]dmentioning
confidence: 99%
“…Calcitriol is known to be a negative endocrine regulator of the RAAS [31]. In several cases, calcitriol treatment was shown to reduce the plasma renin activity, angiotensin II levels, blood pressure, and myocardial hypertrophy [32,33]. In VDR receptor knockout mice, the developing hypertension can be corrected by angiotension converting enzyme inhibitors and angiotensin I receptor antagonists [31].…”
Section: Vitamin D Insufficiency: a Contributing Factor In The Pathogmentioning
confidence: 99%